2007
DOI: 10.1083/jcb.200702081
|View full text |Cite
|
Sign up to set email alerts
|

Zinc is a novel intracellular second messenger

Abstract: Zinc is an essential trace element required for enzymatic activity and for maintaining the conformation of many transcription factors; thus, zinc homeostasis is tightly regulated. Although zinc affects several signaling molecules and may act as a neurotransmitter, it remains unknown whether zinc acts as an intracellular second messenger capable of transducing extracellular stimuli into intracellular signaling events. In this study, we report that the cross-linking of the high affinity immunoglobin E receptor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
458
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 525 publications
(482 citation statements)
references
References 56 publications
12
458
2
3
Order By: Relevance
“…It is unknown the concentration range of cellular zinc that is needed for cypin's effect on dendrite branching. But interestingly, it was previously reported that zinc is released from the perinuclear area, including the endoplasmic reticulum, in mast cells in response to stimulation and can act as a second messenger 21 ; however, it is unknown whether this occurs in neurons and whether this pool of zinc can activate cypin and promote dendrite branching.…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown the concentration range of cellular zinc that is needed for cypin's effect on dendrite branching. But interestingly, it was previously reported that zinc is released from the perinuclear area, including the endoplasmic reticulum, in mast cells in response to stimulation and can act as a second messenger 21 ; however, it is unknown whether this occurs in neurons and whether this pool of zinc can activate cypin and promote dendrite branching.…”
Section: Discussionmentioning
confidence: 99%
“…In the above experiments, Zn 2 + was absent from the extracellular buffer, suggesting that Zn 2 + release occurred from an intracellular source. To exclude the contribution of any contaminating Zn 2 + , we have included the cell-impermeable Zn 2 + chelator, DTPA [30], in the extracellular buffer. DTPA failed to prevent the H 2 O 2 -induced Zn 2 + response; by contrast, the cell-permeable Zn 2 + chelator, TPEN, completely prevented the Zn 2 + response (Figures 2A and 2B).…”
Section: The Source Of Trpm2-targeted Zn 2 + Stores Is Intracellularmentioning
confidence: 99%
“…Zinc modulates the activity of proteins such as receptors and enzymes that are involved in the regulation of numerous processes, including the synthesis of macromolecules, the regulation of signaling cascades and gene transcription, and transport processes. In this capacity, a role for zinc as a second messenger of intracellular signal transduction has recently been recognized (Yamasaki et al 2007). Zinc is also involved in preserving genomic stability through several actions including regulation of redox homeostasis [reviewed in (Oteiza 2012)], DNA repair, synthesis, and methylation (Sharif et al 2012).…”
Section: Biological Functions Of Zincmentioning
confidence: 99%